Prairie Evers - Airgood, Ellen (New York : Nancy Paulsen Books, 2012)
Ten-year-old Prairie is happy being home-schooled and raising her flock of chickens, so transferring to regular school is a big change, but fortunately she meets a wonderful friend.
Accelerated Reader AR
MSBA nominee 2013-14
Keywords: Farm life -- New York (State) -- Juvenile fiction; Families -- New York (State) -- Juvenile fiction; Chickens -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Grandmothers -- Juvenile fiction; New Paltz (N.Y.) -- Juvenile fiction